2011
DOI: 10.1111/j.1365-2788.2011.01415.x
|View full text |Cite
|
Sign up to set email alerts
|

Home literacy environments, interest in reading and emergent literacy skills of children with Down syndrome versus typical children

Abstract: Parents of children with DS tailor home literacy environments to their children's developmental levels. Confirming earlier studies, children with DS achieved some higher literacy skills than what was expected for their MA, emphasising the importance of early reading interventions for this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
38
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 39 publications
6
38
0
4
Order By: Relevance
“…Though limited, previous research has reported fairly rich home literacy environments for individuals with DS (Ricci, 2011). The present study also reflected rich home literacy environments for individuals with DS.…”
Section: Parent Surveysupporting
confidence: 66%
See 3 more Smart Citations
“…Though limited, previous research has reported fairly rich home literacy environments for individuals with DS (Ricci, 2011). The present study also reflected rich home literacy environments for individuals with DS.…”
Section: Parent Surveysupporting
confidence: 66%
“…In her study, Ricci (2011) also reported that the grade-school children with DS with richer home literacy environments indicated more interest in reading than pre-school age children with DS with poorer home literacy environments. The present study was consistent with both Lyytinen et al, (1998) and Ricci's (2011), findings that the home literacy environment is significantly correlated with parent reports of the child's motivation to read. Although not directly tested, rich home literacy environments when the child is very young may lead to increases in the child's motivation to read.…”
Section: Parent Surveymentioning
confidence: 88%
See 2 more Smart Citations
“…Second, according to a parent survey by Trenholm and Mirenda (2006), parents of children with DS do not often ask higherlevel questions, including inferential ones; while the majority reported reading books to their children, only a quarter asked their child questions about what might happen next, or why something happened. Additionally, Ricci (2011) examined the relationship between parents' book reading practices and the language of their children with DS. They found that the type of questions parents asked during book reading correlated with children's reading comprehension and receptive vocabulary.…”
Section: Causal Relationships and Inferencing: Summary And Implicationsmentioning
confidence: 99%